Produção da helicônia golden torch (Heliconia psittacorum x Heliconia spathocircinada) influenciada pela adubação mineral e orgânica,em Alagoas - Rocha, Ernestina Severo (2009)
Alagoana agroflowerculture demonstrates the articulate necessity in the producting clain segments; in order to reduce the costs with insumes like mineral epices, thate represent a significative percentage. The really used managing protects the improvement of the production, but yet there is a lack of special studies abut nutricional standard and informations. This search has had as objective, avaliate the components as production from H. Golden Torch. The experiment was realized in Federal Acrotecnic School. We adapted the experimental delineation in happened blocks, with treatments and five repetition. T1 (Test); T2 (AM); T3 (EGY); T4 (CF); T5 (TF); T6 (CLU), T7 (EG+AM); T8 (CF+AM); T9 (TF+AM) and T10 (CLU+AM). We measure and avaliat variables. Affiliats Number (NPT); stem number(NHF);Length of stem (CHf); diameter of the stem (DHF), Length of the bractea (CB); number of the leaves (NFl) and the follicle area (AFh). The obtained results with the orthogonal contrasts dice showed that contrasts from (T3 to T6) Ks, (T7 to T10) presented 89,3 affiliates less than organominerals treatments. In the contrast (1), treatments didn t manured (Test) with 64,0 floral stems were inferior from medium of all manured treatments. To the stem length, the contrast 4 (EG + CF) was superior in 81,1 cm with (TF + CLU). In the conjoined analysis, the interation Trat x Ano (Treat x year) with F without importance demonstrate that year to NHf, CHf, CB and NFh. We inferred that little productivity were with treatment that we don t use spices and with treatment manured with urban trash cake (pie) of filter.